Interplay between probe design and test performance: overlap between genomic regions of interest, capture regions and high quality reference calls influence performance of WES-based assays - Erinija Pranckeviciene; Lemuel Racacho; Mahdi Ghani; Landry Nfonsam; Ryan Potter; Elizabeth Sinclair-Bourque; Gabrielle Mettler; Amanda Smith; Lucas Bronicki; Lijia Huang; Olga Jarinova (Human Genetics, 2021)

Bacterial diversity along a 2600 km river continuum - Domenico Savio; Lucas Sinclair; Umer Z. Ijaz; Juraj Parajka; Georg H. Reischer; Philipp Stadler; Alfred P. Blaschke; Günter Blöschl; Robert L. Mach; Alexander K. T. Kirschner; Andreas H. Farnleitner; Alexander Eiler (Environmental Microbiology, 2015)
Summary The bacterioplankton diversity in large rivers has thus far been under‐sampled despite the importance of streams and rivers as components of continental landscapes. Here, we present a comprehensive dataset detailing the bacterioplankton diversity along the midstream of the D anube River and its tributaries. Using 16 S rRNA ‐gene amplicon sequencing, our analysis revealed that bacterial richness and evenness gradually declined downriver in both the free‐living and particle‐associated bacterial communities. These shifts were also supported by beta diversity analysis, where the effects of tributaries were negligible in regards to the overall variation. In addition, the river was largely dominated by bacteria that are commonly observed in freshwaters. Dominated by the acI lineage, the freshwater SAR 11 ( LD 12) and the P olynucleobacter group, typical freshwater taxa increased in proportion downriver and were accompanied by a decrease in soil and groundwater‐affiliated bacteria. Based on views of the meta‐community and River Continuum Concept, we interpret the observed taxonomic patterns and accompanying changes in alpha and beta diversity with the intention of laying the foundation for a unified concept for river bacterioplankton diversity.